Impact of Naked Neck (Na) and Frizzle (F) Genes on Growth Performance and Immunocompetence in Chickens - Mahrous, M.; Galal, A.; Fathi, M.M.; El-Dein, A. Zein (International Journal of Poultry Science, 2007)
Growth performance and immune response of naked neck, frizzle and double segregation chickens were evaluated under moderate temperature. Four genetic groups originated from the same genetic origin (normally feathered, frizzled, naked neck and naked neck-frizzled) were used in the current study. Body weight and feed conversion ratio were determined from 4-12 weeks of age. Humoral immunity, phagocytic ability, cell-mediated immunity and relative weight of lymphoid organs were determined. The frizzled (nanaFf), naked neck (Nanaff) and naked neck frizzled (NanaFf) genotypes had significantly heavier body weight compared to normally feathered (nanaff) counterparts. The presence of Na gene in a single state or interacted with F gene significantly improved feed conversion ratio compared to nanaff sibs. With respect to immunocompetence measurements, it could be noticed that the Na, F and double segregation genes significantly increased total antibody titer against sheep red blood cells (SRBCs) compared to nanaff genotype. Concerning cautenous basophilic hypersensitivity (CBH), it could be speculated that the naked neck, frizzle and naked neck frizzle birds were hyper responder to phytohemagglutinin-P (PHA-P) injection compared to normally feathered sibs. Likewise, naked neck, frizzled and naked neck-frizzled birds had significantly higher carbon clearance index (lower carbon particles in their blood circulation) compared to normally feathered counterparts. Negative relationship between body weight and relative weight of lymphoid organs was observed in all genetic groups. Also, there was significantly negative correlation between body weight and total antibody against SRBCs in all genotypes. The phagocytic ability measured at all times was negatively correlated with body weight in all genetic groups. It could be concluded that the naked neck, frizzled genes in a single state or in combination significantly increased immune response of chicken under prevailing conditions of Egypt. Therefore, introducing naked neck (Na) and frizzle (F) genes in selection programs for disease-resistance must be taken into consideration, particularly in unfavorable environments.